Big Data and Predictive Analytics for Indonesia's Economic Transformation and Digital Resilience - Maspul, Kurniawan Arif; Putri, Nugrahani Kartika (Journal of Technology and System Information, 2025)
In an era defined by data, Big Data and Predictive Analytics have become indispensable tools for driving economic growth, innovation, and resilience. For Indonesia, one of Southeast Asia’s most dynamic digital economies, these technologies offer a transformative pathway to industrial modernization and global competitiveness. With over 212 million internet users and a digital economy projected to hit $146 billion by 2025, Indonesia is poised to harness the power of data to revolutionize sectors such as finance, healthcare, e-commerce, and manufacturing (Antara News, 2022). This study delves into the multifaceted landscape of Big Data in Indonesia, offering a comprehensive analysis of its economic potential and implementation challenges. It highlights how predictive analytics is reshaping industries, enabling businesses to optimize supply chains, enhance customer experiences, and mitigate risks with unprecedented precision. At the same time, it addresses pressing concerns such as data privacy, cybersecurity vulnerabilities, and the ethical implications of AI-driven decision-making. To unlock the full potential of Big Data, this study proposes actionable policy recommendations, including investments in data infrastructure, the development of ethical AI frameworks, and the expansion of STEM education and workforce training programs. Indonesia can create a long-term data ecosystem that balances innovation and responsibility by encouraging collaboration among government, industry, and academics. As Indonesia stands at the crossroads of the Fourth Industrial Revolution, the strategic integration of Big Data and Predictive Analytics is no longer optional—it is imperative. This study serves as a roadmap for Indonesia to harness the power of data, ensuring that these technologies drive not only economic growth but also inclusive development and digital resilience in an increasingly data-driven world.